Effect of combustion regime on in-cylinder heat transfer in internal combustion engines. (March 2016) - Jia, Ming; Gingrich, Eric; Wang, Hu; Li, Yaopeng; Ghandhi, Jaal B; Reitz, Rolf D
A multi-dimensional model was applied to investigate the influence of combustion regimes on heat transfer losses in internal combustion engines. By utilizing improved turbulence and heat transfer sub-models, the combustion and heat transfer characteristics of the engine were satisfactorily reproduced for operation under conventional diesel combustion, homogeneous charge compression ignition, and reactivity controlled compression ignition regimes. The results indicated that the total heat transfer losses of conventional diesel combustion are the largest among the three combustion regimes due to the direct interaction of the high-temperature flame with the piston wall, while the heat transfer losses of reactivity controlled compression ignition are the lowest and nearly are independent of combustion phasing because of the avoidance of high-temperature regions adjacent to the cylinder walls. Compared to conventional diesel combustion, homogeneous charge compression ignition shows more potential for the reduction of exhaust energy and improvement of fuel efficiency. In reactivity controlled compression ignition combustion, the reduction of heat transfer and exhaust losses outweigh its increase in combustion losses and offer the opportunity for further improvement of fuel efficiency. Furthermore, by evaluating the widely used Woschni and Chang et al.'s empirical heat transfer correlations, it was found that both correlations considerably overestimate the heat transfer rate for the reactivity controlled compression ignition regime. It is necessary to improve empirical heat transfer models to take account of the flow and combustion characteristics under various combustion modes.